A novel controller for PV-fed water pumping optimization system driven by an 8/6 pole SRM with asymmetrical converter - Kumar Kolluru, Ashok; Malligunta, Kiran Kumar; Teja, S. Ravi; Reddy, Ch. Rami; Alqahtani, Mohammed; Khalid, Muhammad (Frontiers in Energy Research, 2023)
A locally installed photovoltaic (PV)-powered motor pump is a viable solution for a water pumping system (WPS) in rural locations. In this study, a single-stage, PV-fed, SRM-powered WPS was investigated and realized using a speed sensorless sliding mode controller (SMC)-based direct torque control (DTC). As a result, no additional DC-DC converter was required for maximum power absorption from the PV source. By utilizing a novel high-side switch asymmetric converter with a hybrid Perturb and Observe–Grey Wolf optimization (POGWO) method integrated with a DC-link voltage controller, an efficient single-stage conversion was achieved. The robustness of the proposed integrated control is presented by comparing it with a Genetic Algorithm and Particle Swarm Optimization (PSO). Extensive results using MATLAB SIMULINK are shown to validate the proposed system in both steady-state and transient conditions for various partial shading conditions.